Physical exercise-associated gene expression signatures in peripheral blood - Kawai, T; Morita, K.; Masuda, K.; Nishida, K.; Sekiyama, A.; Teshima-Kondo, S.; Nakaya, Y.; Ohta, M.; Saito, T.; Rokutan, K. (Clinical Journal of Sport Medicine, 2007)
Objective: To assess response to physical stress, gene expression profiles in peripheral blood cells were analyzed using an original microarray carrying 1467 stress-responsive complementary DNA probes.